Coating diaphragm, preparation method thereof and secondary battery
By using coating membrane technology on lithium-ion battery separators and using the coating layer of inorganic particles, the problems of cracks and fall off after the separator are cut are solved, the risk of short-circuit of the battery cell is reduced, and the stability of thermal shrinkage performance is maintained.
Patent Information
- Application Number
- CN202411996531.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The lithium-ion battery separator is prone to cracks and fall off after being cut, resulting in an increase in the risk of short-circuit of the battery cell and unstable thermal shrinkage performance.
A coated separator is adopted, which includes a base film and a coating layer covering one side of the base film. The coating layer contains inorganic particles. By optimizing the preparation process of the base film and the coating layer, the characteristics of cracks and shedding are controlled within a certain range.
It effectively alleviates cracks and fall off after cutting the coated diaphragm, reduces the risk of battery cell short circuit, and maintains the stability of the thermal shrinkage performance of the diaphragm.
Smart Images

Figure CN119786880A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a coated separator and a preparation method thereof, and a secondary battery. Background Art
[0002] The current materials of lithium-ion battery separators are usually polyolefin materials, which have poor heat resistance. When the battery temperature reaches the melting temperature of the separator, the separator melts and breaks, and the positive and negative electrodes will come into direct contact and produce an internal short circuit. At the same time, polyolefin separators have poor wettability to electrolytes, which makes the lithium-ion battery injection and liquid retention effects poor, thereby adversely affecting the performance of lithium-ion batteries. The main method to deal with the above problems is to coat the surface of the separator with corresponding functional coatings, such as inorganic ceramic coatings. Coating a single-sided or double-sided inorganic ceramic coating on the surface of the separator can effectively improve the heat resistance of the separator, support the separator base film at high temperatures, and reduce the thermal shrinkage of the separator. At the same time, inorganic ceramic coating can also improve the wetting effect of the separator on the electrolyte.
[0003] Winding is a key process in the manufacturing of lithium-ion batteries. First, the tabs are ultrasonically welded to the current collector, and then the positive and negative pole pieces and separators are arranged in the order of positive electrode-separator-negative electrode-separator, and then assembled into cylindrical or square cells by winding. When battery manufacturers wind the cells, the entire roll of separator will be cut off (usually with a serrated knife) after each winding is completed. Summary of the invention
[0004] The inventors found that the coated diaphragm will have some defects near the fracture after being cut. Although it cannot be observed with the naked eye, microscopic observation can reveal cracks in the coating and even powder falling off. In the continuous production process of the battery cell, every time the diaphragm is cut, cracks and coating shedding will cause dust on the site. This dust will continue to gather and cause certain damage to the battery cell after being drawn into the battery cell, increasing the risk of short circuit of the battery cell. In addition, severe cracks and shedding will cause a significant increase in the thermal shrinkage of the diaphragm, which will also cause a short circuit between the positive and negative electrodes during the charging and discharging process of the battery cell.
[0005] In view of the above problems, the present invention provides a coated diaphragm and a preparation method thereof, and a secondary battery, which can alleviate the occurrence of cracks and falling off of the coated diaphragm after it is cut.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0007] A first aspect of the present invention provides a coated diaphragm, comprising: a base film and a coating layer covering one or both sides of the base film, wherein the coating layer comprises inorganic particles;
[0008] After the coated diaphragm is cut with a serrated knife (cut along the TD direction), cracks and / or shedding appear in the coating near the fracture, and any cracks and / or shedding meet the following characteristics:
[0009] 1) The length of the crack in the MD direction is less than 20 μm and the crack width is less than 20 nm; and
[0010] 2) The area of the peeling area is less than 1μm 2 .
[0011] It should be noted that the serrated knife described in the present invention refers to a knife with a blade covered with serrations, as opposed to a flat-blade knife without serrations. The serrated knife has a serration pitch of 0.5 to 10 mm and can be a serrated knife of a model or specification suitable for various battery manufacturers.
[0012] The following is a detailed description:
[0013] Basement membrane:
[0014] There is no particular restriction on the type of the base film, which can be selected according to actual needs; preferably, the base film can be selected from one or more of polyethylene film, polypropylene film, polyethylene / polypropylene composite film, polyimide film, polyvinylidene fluoride film, polyvinylidene fluoride-hexafluoropropylene film, polyamide film, and polyethylene terephthalate film, preferably a polyethylene film.
[0015] The thickness of the base film may be 4-20 μm, preferably 5-12 μm.
[0016] The porosity of the base film may be 25-70%, preferably 30-65%, and more preferably 35-42%.
[0017] The MD elongation at break of the base film is ≤100%, preferably 50-90%.
[0018] The elongation at break refers to the ratio of the length increased by stretching the base film until it breaks in the MD direction at room temperature to the initial length, and its unit is "%". The elongation at break can be measured by a tensile test.
[0019] Coating:
[0020] The coating layer includes inorganic particles;
[0021] The inorganic particles are one or more selected from α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide, and silicon carbide;
[0022] The average particle size D50 of the inorganic particles is preferably 0.1-1.5 μm, more preferably 0.2-0.8 μm.
[0023] The specific surface area S of the inorganic particles is preferably 1-25 m 2 / g.
[0024] The specific surface area (BET) can be measured by a specific surface area tester and refers to the sum of specific surface areas per unit weight.
[0025] In some embodiments, the coating layer further comprises an organic polymer material;
[0026] The organic polymer material is one or more organic powders or suspensions selected from polyimide, polyetherimide, aramid, aramid sulfone, polyvinylidene fluoride, polymethyl methacrylate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene and the like.
[0027] In some embodiments, the coating layer further comprises a first binder and a second binder;
[0028] The first binder is an acid binder, which may be acrylic acid, polyacrylic acid, or carboxylic acid;
[0029] The second adhesive is an ester adhesive, which may be acrylate, polyacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, or ethyl methacrylate.
[0030] Preferably, the coating layer comprises the following components in mass percentage: 80-96% inorganic particles, 1-6% first binder, 1-6% second binder, and 3-12% organic polymer material.
[0031] The above mass percentages all refer to the dry weight of the above components. The binder and the organic polymer material can also be added in the form of emulsion or solution.
[0032] Preferably, the coating layer has a thickness of 0.1-5 μm.
[0033] The coated diaphragm of the present invention is placed on a tensile machine (tightened in the MD direction), and a serrated knife is used to vertically cut the diaphragm (the blade is perpendicular to the diaphragm surface). The cut diaphragm is placed under a 1K-fold electron microscope for observation. The diaphragm coating has cracks and / or falls off (powder falls off) near the fracture (from the outside to the inside of the fracture, perpendicular to the fracture boundary within a length range of 30 μm), such as Figure 1 As shown, cracks refer to the streaky cracks on the coating, and shedding refers to the blocky powder-shedding areas on the coating. The cracks and / or shedding have the following characteristics:
[0034] 1) The (vertical) length of any crack in the direction perpendicular to the cutting (fracture, or cross section) (i.e., the processing direction, or MD direction, or longitudinal direction) is less than 20 μm, preferably 5-15 μm, such as 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 μm, etc.; the crack usually starts from the fracture (starting end) and extends inward. When measuring, a line parallel to the fracture is drawn at the tail end of the crack, and the vertical distance from the starting end of the crack to the line is the specified length, such as Figure 1 As shown in a;
[0035] The width of any crack is less than 20 nm, preferably 5-15 nm, for example 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 nm, etc. During measurement, the width of the widest part in the crack extension direction can be measured under an electron microscope.
[0036] 2) The area of any powder falling off area in the direction perpendicular to the cutting (fracture, or cross section) (i.e. the processing direction, or MD direction, or longitudinal direction) is less than 1μm 2 , for example 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 μm 2 etc.; imageJ software can be used for measurement (insert the electron microscope image into the software, draw the trajectory of the powder falling off area, and then obtain the internal area of the trajectory), such as Figure 1 The range shown in b.
[0037] In some embodiments, any cracks and / or shedding satisfy the following characteristics:
[0038] 1) The length of the crack along the MD direction is less than 15μm and the crack width is less than 15nm; and
[0039] 2) The area of the coating peeling area along the MD direction is less than 1μm 2 .
[0040] The above characteristics can reflect some inherent characteristics of the coated diaphragm, which include but are not limited to the slip adhesion between the base film and the coating, the bonding force between the base film and the coating, the cohesion between the particles inside the coating, etc. These characteristics are quantitatively manifested through the above characteristics after being cut by a serrated knife. The proportion and size of the cracks and / or detachment areas generated after the coated diaphragm of the present invention is cut are within the above range, and the thermal shrinkage performance of the diaphragm does not change significantly during the cutting process of the battery cell processing serrated knife, thereby avoiding the risk of short circuit of the battery cell. Beyond the above range, cracks and detachment are obvious, which will cause the thermal shrinkage performance of the diaphragm to be poorly stable and easily cause a short circuit.
[0041] In an embodiment of the present invention, the difference between the heat shrinkage rate in the MD direction of the sample cut by a serrated knife and kept at 150°C for 1 hour and the heat shrinkage rate in the MD direction of the sample cut by a flat knife and kept at 150°C for 1 hour does not exceed 10%.
[0042] Preferably, the heat shrinkage rate of the coated separator in the MD direction after being kept at 150° C. for 1 hour is less than 15%;
[0043] The coated separator has a heat shrinkage in the MD direction of less than 18% after being cut with a flat knife and kept at 150° C. for 1 hour.
[0044] The thermal shrinkage rate of the coated diaphragm in the MD direction after being cut with a serrated knife and kept at 150° C. for 1 hour is less than 25%;
[0045] The thermal shrinkage rate can be tested by a method known in the art. As a specific example, the test is performed according to the requirements of GB / T36363-2018.
[0046] MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) ÷ MD length before heating × 100;
[0047] When the coated diaphragm is cut with a sharp flat-blade knife, the thermal shrinkage does not change significantly compared with the uncut coated diaphragm. However, battery factories generally use serrated knives to cut battery cells, and after cutting with serrated knives, powder loss and cracks are obvious, and thermal shrinkage is significantly increased. The powder loss and cracks of the coated diaphragm of the present invention are controlled within a certain range, and the thermal shrinkage performance of the diaphragm does not increase significantly after cutting with a serrated knife.
[0048] In the embodiment of the present invention, the powder loss rate of the coated diaphragm after being cut by a serrated knife (each time) is less than 0.6%, preferably 0.2-0.4%.
[0049] The cutting powder loss rate is the powder loss rate of the coated diaphragm after cutting compared with that before cutting.
[0050] The coating diaphragm of the present invention has a low powder loss rate during cutting.
[0051] A second aspect of the present invention provides a method for preparing a coated diaphragm, comprising the following steps:
[0052] Preparation of basement membrane:
[0053] (1) Extrusion: The diluent and polyethylene are heated and melted in an extruder to form a uniform mixed melt; the viscosity average molecular weight of the polyethylene is ≤ 2 million;
[0054] (2) Casting: The mixed melt obtained in (1) is flowed out to a casting roll for cooling, phase separation, cooling and forming, and obtaining a film;
[0055] (3) Pre-stretching: heating the film obtained in (2) and biaxially stretching it to orient the molecular chains; MD stretching ratio>1, 1<MD stretching ratio / TD stretching ratio<2;
[0056] (4) Biaxial stretching: heating the film obtained in (3) and biaxially stretching it to orient the molecular chains; the results of the two-step stretching in steps (3) and (4) are that the MD stretching ratio is greater than 8 times, and 1 is less than the MD stretching ratio / TD stretching ratio is less than 2;
[0057] (5) Extraction and drying: using an extractant to elute the diluent remaining in the biaxially stretched membrane in step (4), and drying;
[0058] (6) Transverse stretching and shaping: the dried film obtained in step (5) is transversely stretched and shaped, and then rolled up to obtain a base film;
[0059] The MD elongation at break of the obtained base film is ≤100%;
[0060] Coating:
[0061] (7) dispersing the inorganic particles, the first binder, the second binder and the optional organic polymer material in a solvent, and mixing them uniformly to obtain a coating slurry;
[0062] Taking the dry weight of the coating slurry as 100%, the coating slurry includes the following components in mass percentage: 80-96% of inorganic particles, 1-6% of a first binder, 1-6% of a second binder, and 0-12% of an organic polymer material;
[0063] The numerical relationship between the specific surface area S of the inorganic particles and the total mass proportion M of the first binder and the second binder satisfies: S / 0.5≥M≥S / 5, where the unit of S is m 2 / g, the unit of M is %;
[0064] (8) The coating slurry is applied on at least one surface of the base film and dried to obtain a coated separator.
[0065] The following is a detailed description:
[0066] Preparation of basement membrane:
[0067] According to an embodiment of the present disclosure, the diluent in step (1) is a mixture of C18 to C30 hydrocarbons;
[0068] Preferably, the diluent is a mixture of C18-C30 liquid hydrocarbons with a molecular weight of 200-600;
[0069] Further preferably, the diluent is paraffin oil.
[0070] According to an embodiment of the present disclosure, the mass ratio of polyethylene to diluent in step (1) is (10-30): (70-90);
[0071] According to an embodiment of the present disclosure, the heating and melting temperature in step (1) is 160°C to 210°C.
[0072] According to an embodiment of the present disclosure, the temperature of the casting roller in step (2) is ≤30°C, preferably ≤25°C.
[0073] According to an embodiment of the present disclosure, the biaxial stretching temperature in step (4) is 119°C to 135°C.
[0074] According to an embodiment of the present disclosure, the extractant in step (5) is dichloromethane.
[0075] According to the embodiment of the present disclosure, in step (5), the drying temperature is 25 to 80° C., and the drying time is 10 to 100 seconds.
[0076] According to an embodiment of the present disclosure, in step (6), the transverse stretching temperature is 100° C. to 140° C., and the TD (transverse) stretching ratio is 1.1 to 1.8 times.
[0077] According to the embodiment of the present disclosure, in step (6), the shaping temperature is 120° C. to 140° C., and the shaping time is 0.1 s to 60 s.
[0078] MD or TD stretching ratio = length after stretching / length before stretching.
[0079] Coating:
[0080] The present invention controls the numerical relationship between the specific surface area S of the inorganic particles and the total mass proportion M of the first binder and the second binder to satisfy the following: S / 0.5≥M≥S / 5. Too much binder will lead to excessive cohesion, which may easily cause the inorganic particles to fall off in blocks. Too little binder may easily cause cracks.
[0081] The above relationship is in S units m 2 / g, M in %, the relationship between the values substituted (without units). M refers to the mass percentage of the total dry weight of the first binder and the second binder in the coating layer to the dry weight of the coating slurry.
[0082] According to an embodiment of the present disclosure, the solvent in step (7) is at least one selected from water, N-methylpyrrolidone, and N,N-dimethylacetamide.
[0083] According to the embodiment of the present disclosure, in step (7), the mixing speed is 800N2000rpm, and the mixing time is 20 to 100min.
[0084] In addition to the above raw materials, the coating slurry may also contain other arbitrary components, such as viscosity modifiers, dispersants, wetting agents, electrolyte dispersion inhibitors, etc. The above components are not particularly limited as long as they do not cause adverse effects on the lithium battery, and the above arbitrary components may be one, two or more.
[0085] There is no particular restriction on the coating method of the slurry, and coating methods such as coating method and dipping method can be selected for coating. As coating methods, methods such as scraper method, reverse roll method, direct roll method, micro gravure roll method, extrusion method, spraying method, and spot coating method can be cited. Considering the uniformity of the thickness of the porous film, it is preferred that the micro gravure roll method is used for coating.
[0086] There is no particular limitation on the drying method, and drying methods such as hot air, low-humidity air, vacuum drying, spray drying, and freeze drying can be selected.
[0087] In the base film preparation stage, the relative slip between the base film and the coating is adjusted. If the elastic deformation of the base film is too different from that of the coating, the coating will be broken, so the MD elongation at break should be lowered. The present invention adjusts the base film preparation raw materials and preparation process parameters so that the MD elongation at break of the base film is ≤100%.
[0088] In the coating stage, the adhesion between the coating and the base film and the cohesive adhesion between the particles should be improved. The present invention improves the crack and powder loss problems after cutting by adjusting the amount of two different binders and controlling the relationship between the BET of the inorganic particles and the total mass ratio of the binder.
[0089] Through the improvement of the above two stages of base film and coating, the relative slippage of the base film and coating after cutting is controlled, and the adhesion between the coating and the base film and the cohesion between the particles inside the coating are improved. The two stages cooperate with each other to significantly improve the cracking and falling off problems of the diaphragm after cutting.
[0090] According to the method provided in the second aspect of the embodiment of the present invention, a coated diaphragm according to any embodiment of the first aspect of the present invention can be obtained.
[0091] The diaphragm provided by the present invention is not limited to being prepared by the preparation method provided by the present invention.
[0092] According to a third aspect of the present invention, a secondary battery is provided, comprising the coated diaphragm provided in the first aspect of the embodiment of the present invention or the coated diaphragm prepared by the preparation method provided in the second aspect of the embodiment of the present invention.
[0093] The coated diaphragm provided in the embodiment of the present invention can be used in different types of batteries, so there is no particular restriction on the type of battery, and it can be selected according to actual needs. Preferably, it can be used in secondary batteries, especially secondary batteries containing liquid electrolytes, such as lithium ion batteries, sodium ion batteries, etc.
[0094] Beneficial effects:
[0095] The diaphragm provided by the present invention can alleviate the occurrence of cracks and shedding after the coated diaphragm is cut. Furthermore, the present invention also provides a preparation method, by changing the raw materials and process parameters for base film preparation in the base film section, and adjusting the ratio of the two binders and the relationship between the BET of the inorganic particles and the total mass proportion of the binder in the coating section, the two binders cooperate with each other to alleviate the crack and shedding problems of the diaphragm after cutting, so that the crack and shedding are significantly improved, and the short circuit of the battery cell is avoided.
[0096] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0097] Figure 1 The cracks and shedding conditions of the coated diaphragm of the present invention after cutting. DETAILED DESCRIPTION
[0098] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0099] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0100] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0101] Test method:
[0102] Elongation at break: The test was conducted in accordance with the provisions of GB / T 1040.3-2006. A sample of 2.5 cm × 20 cm was cut and marked as the diaphragm in MD / TD direction. The sample was tested using a tensile testing machine (Jinan Sike Testing Technology Co., Ltd., TSL-1002). The sample was fixed between the upper and lower clamps of the tensile testing machine (the distance between the clamps was 100 ± 5 mm). The sample was ensured to be flat and wrinkle-free, vertical and not skewed. The tensile speed was 250 mm / min. Based on the width and thickness of the sample, the test was conducted three times and the average value was taken as the elongation at break (%) in the MD / TD direction.
[0103] Heat shrinkage rate: Cut a sample of 10 cm × 10 cm in size, mark the transverse TD and longitudinal MD on the sample, measure the transverse and longitudinal widths with a fully automatic image measuring projector (Kunshan Gaopin Precision Instrument Co., Ltd., GP-300C), clamp the sample between two sealed A4 papers, place the sample in a 150°C oven for 1 hour, and measure the transverse and longitudinal widths with a fully automatic image measuring projector after the sample returns to room temperature. Measure 3 times and take the average value. The heat shrinkage rate can be calculated by the following formula: MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) ÷ MD length before heating × 100;
[0104] Cutting powder loss rate: Before cutting, place the diaphragm on an analytical balance and weigh it, and record the weight as ml. After cutting with a serrated knife, place the cut diaphragm on an analytical balance and weigh it, and record the weight as m2. Powder loss amount M (mg) = m1-m2, powder loss rate = M / m1×100%.
[0105] Preparation Examples 1 to 9 Preparation of Base Films
[0106] The polyethylene in the preparation example is polyethylene with an average molecular weight (viscosity average) of 1.5 million (manufacturer: Celanese, model: GURX223), and the equipment used is the wet-process diaphragm line of Sinoma Lithium Membrane Co., Ltd.
[0107] (1) Extrusion: Paraffin oil and polyethylene are respectively conveyed to an extruder in proportion, and the paraffin oil-polyolefin resin mixed system is heated and melted at 180° C. in the extruder to form a uniform mixed melt;
[0108] (2) Casting: The mixed melt obtained in (1) is flowed out to a casting roll for cooling, the casting roll temperature is ≤20°C, phase separation is performed, and cooling is performed to form a sheet;
[0109] (3) Pre-stretching: The film obtained in (2) is heated and biaxially stretched to orient the molecular chains; the MD stretching ratio is 1.4 times and the TD stretching ratio is 1 times;
[0110] (4) Biaxial stretching: heating the film obtained in (3) and biaxially stretching it to orient the molecular chains; the results of the two-step stretching in steps (3) and (4) meet the requirements in Table 1;
[0111] (5) Extraction: using dichloromethane to elute the extractant remaining in the biaxially stretched membrane in step (4); drying the extracted membrane at 35° C. for 21 seconds;
[0112] (6) Transverse stretching: The dried film obtained in step (4) is stretched transversely and shaped.
[0113] The relevant parameters of the base film of each preparation example are shown in Table 1.
[0114] Preparation Examples 1 to 9 Coating Slurry Preparation
[0115] Boehmite, PMMA emulsion (Shenzhen Haodian Technology Co., Ltd., SWA709, solid content 20%), polyacrylic acid emulsion (Hunan Gaorui Power Material Co., Ltd., LIB-S105B, solid content 21%), polyacrylate emulsion (Japan ZEON Co., Ltd., BM-900B, solid content 40%), sodium carboxymethyl cellulose, polyether modified siloxane and water were prepared into an aqueous coating slurry by stirring at 1300 rpm for 60 hours.
[0116] The relevant parameters of the coating slurry of each preparation example are shown in Table 1.
[0117] Table 1
[0118]
[0119]
[0120] Test Examples 1 to 13 Preparation of Coated Diaphragms
[0121] The base film and coating slurry of each example are shown in Table 2.
[0122] Coating process: The aqueous coating slurry is gravure coated on one side of the base film by an MCD type coater, and finally dried in an oven at 70° C. for 12 seconds.
[0123] The coated diaphragms of the embodiment and the comparative embodiment are placed on a tensile testing machine to be stretched in the MD direction, and are cut vertically with a serrated knife. The cut diaphragms are observed under a 1K electron microscope, and the size of the maximum crack and the powder loss area within 30 μm near the fracture are recorded (the method is the same as before).
[0124] After the coated diaphragms of the examples and comparative examples were cut with a serrated knife using the above method, the thermal shrinkage rate of the cut samples at 150°C for 1 hour was tested; after the coated diaphragms of the examples and comparative examples were cut with a flat knife instead of a serrated knife using the above method, the thermal shrinkage rate of the cut samples at 150°C for 1 hour was tested.
[0125] After the coated separators of the examples and comparative examples were cut with a serrated knife in the above method, the weight loss before and after cutting of the samples was measured, and the cutting powder rate was calculated.
[0126] The test results of each embodiment and comparative embodiment are shown in Table 2.
[0127] Table 2
[0128]
[0129]
[0130] It can be seen from the above test examples 1 to 5, 7 to 12 that the maximum crack length in the MD direction of the diaphragm of the present application is less than or equal to 12nm, the maximum crack width is less than or equal to 4nm, and the area of the powder falling off region is less than or equal to 0.8μm 2 , the heat shrinkage rate after cutting with a serrated knife is less than 15%, and the powder loss rate after cutting with a serrated knife is less than 0.5%. Especially when the elongation at break of the base film is 50-90%, it has a smaller heat shrinkage rate after cutting with a serrated knife.
[0131] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A coated diaphragm, characterized in that: include: A base film and a coating layer covering one or both sides of the base film, wherein the coating layer comprises inorganic particles; After the coated diaphragm is cut with a serrated knife, cracks and / or shedding occurs in the coating near the fracture, and any cracks and / or shedding meets the following characteristics: 1) The length of the crack in the MD direction is less than 20 μm and the crack width is less than 20 nm; and 2) The area of the peeling area is less than 1μm 2 .
2. The coated diaphragm according to claim 1, characterized in that The difference between the heat shrinkage rate in the MD direction of the coated separator after being cut with a serrated knife and kept at 150° C. for 1 hour and the heat shrinkage rate in the MD direction of the coated separator after being cut with a flat knife and kept at 150° C. for 1 hour is not more than 10%.
3. The coated diaphragm according to claim 1, characterized in that The powder loss rate of the coated diaphragm after being cut by a serrated knife is less than 0.6%.
4. The coated diaphragm according to any one of claims 1 to 3, characterized in that: The MD breaking elongation of the base film is ≤100%.
5. The coated diaphragm according to any one of claims 1 to 3, characterized in that: The coating layer further comprises a first binder, a second binder and an optional organic polymer material; The first binder is at least one selected from acrylic acid, polyacrylic acid, and carboxylic acid binders; The second binder is at least one selected from acrylate, polyacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, and ethyl methacrylate; The organic polymer material is at least one selected from the group consisting of polyimide, polyetherimide, aramid, aramid sulfone, polyvinylidene fluoride, polymethyl methacrylate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene.
6. The coated diaphragm according to claim 5, characterized in that The coating layer comprises the following components in mass percentage: 80-96% inorganic particles, 1-6% first binder, 1-6% second binder, and 0-12% organic polymer material.
7. A method for preparing a coated diaphragm according to any one of claims 1 to 6, characterized in that: The following steps are involved: Preparation of basement membrane: (1) Extrusion: The diluent and polyethylene are heated and melted in an extruder to form a uniform mixed melt; the viscosity average molecular weight of the polyethylene is ≤≤2 million; (2) Casting: The mixed melt obtained in (1) is flowed out to a casting roll for cooling, phase separation, cooling and forming, and obtaining a film; (3) Pre-stretching: heating the film obtained in (2) and biaxially stretching it to orient the molecular chains; MD stretching ratio>1, 1<MD stretching ratio / TD stretching ratio<2; (4) Biaxial stretching: heating the film obtained in (3) and biaxially stretching it to orient the molecular chains; the results of the two-step stretching in steps (3) and (4) are that the MD stretching ratio is greater than 8 times, and 1 is less than the MD stretching ratio / TD stretching ratio is less than 2; (5) Extraction and drying: using an extractant to elute the diluent remaining in the biaxially stretched membrane in step (4), and drying; (6) Transverse stretching and shaping: the dried film obtained in step (5) is transversely stretched and shaped, and then rolled up to obtain a base film; The MD elongation at break of the obtained base film is ≤100%; Coating: (7) dispersing the inorganic particles, the first binder, the second binder and the optional organic polymer material in a solvent, and mixing them uniformly to obtain a coating slurry; Taking the dry weight of the coating slurry as 100%, the coating slurry includes the following components in mass percentage: 80-96% of inorganic particles, 1-6% of a first binder, 1-6% of a second binder, and 0-12% of an organic polymer material; The numerical relationship between the specific surface area S of the inorganic particles and the total mass proportion M of the first binder and the second binder satisfies: S / 0.5≥M≥S / 5, where the unit of S is m 2 / g, the unit of M is %; (8) The coating slurry is applied on at least one surface of the base film and dried to obtain a coated separator.
8. The preparation method according to claim 7, characterized in that: In step (1), the mass ratio of polyethylene to diluent is (10-30):(70-90).
9. The preparation method according to claim 7, characterized in that: In step (4), the biaxial stretching temperature is 119° C. to 135° C.; In step (6), the transverse stretching temperature is 100°C to 140°C, and the TD stretching ratio is 1.1 to 1.8 times.
10. A secondary battery, characterized in that: The invention comprises the coated diaphragm according to any one of claims 1 to 6 or the coated diaphragm prepared by the preparation method according to any one of claims 7 to 9.
Citation Information
Patent Citations
Separator for nonaqueous secondary batteries, and nonaqueous secondary battery
CN104838519A
Diaphragm, preparation method thereof, secondary battery and electric equipment
CN113594631A
Ultrahigh-strength diaphragm and preparation method thereof
CN114914631A
Preparation method of lithium battery diaphragm
CN116706419A
High-porosity, high-permeability lithium ion battery base film and preparation method therefor, and lithium ion battery
WO2023045384A1
Cited By
Coating separator and preparation method therefor, and secondary battery
WO2026145843A1